Bioprosthetic valve monitoring in patients with carcinoid heart disease - Honan, Kevin A.; Hassan, Saamir; Deswal, Anita; Herrmann, Joerg; Song, Juhee; Monlezun, Dominique; Halperin, Daniel; Mahvash, Armeen; Dasari, Arvind; Koutroumpakis, Efstratios; Akay, Mehmet; Balanescu, Dinu-Valentin; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Carcinoid heart disease (CnHD) is a frequent cause of morbidity and mortality in patients with neuroendocrine tumors and carcinoid syndrome. Although valve replacement surgery appears to decrease all-cause mortality in patients with advanced CnHD, few studies have investigated the outcomes of patients after valve replacement. Methods We conducted a multi-institution retrospective registry of patients who received both tricuspid and pulmonic bioprosthetic valve (TV/PV) replacements for advanced CnHD from November 2005 to March 2021. Patients were followed post-operatively with echocardiographic studies every 3 months. Carcinoid valvular heart disease scores were used to monitor valve degeneration. Neuroendocrine tumor treatment, their administration times, and associations with echocardiographic findings were recorded. Results Of 87 patients with CnHD, 22 patients underwent simultaneous surgical TV and PV replacement. In 6 patients (27.3%), increased PV Vmax was the first echocardiographic manifestation of valve degeneration in the setting of occult neurohormonal release. Post-operative telotristat ethyl and peptide receptor radionuclide therapy appeared to stabilize PV Vmax. The PV Vmax showed consistent elevation in the entire patient population when compared to baseline, while bioprosthetic TV echocardiographic parameters were relatively unchanged throughout. Post-operative warfarin therapy did not affect the rate of PV degeneration, and no major bleeding was recorded during or after post-operative anticoagulation therapy. Conclusion Bioprosthetic valve degeneration is common in CnHD. Monitoring with echocardiographic studies every 3 months, focusing on PV velocities, could identify patients with occult disease that very likely promotes valve degeneration. Novel neuroendocrine tumor therapies may have a beneficial impact on valve degeneration.